Development of an Interactive Augmented Reality-Based Weather Forecast Simulation with Automated BMKG Data for Enhanced TV Broadcasting - Zikky, Moh.; Alexander, Robby; Eka Darmawan, Zakha Maisat; Humaira, Fitrah Maharani; Safira, Laily Asna (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
The weather has a significant impact on human activities. Weather data are used in various industries. Recently, Augmented Reality (AR) technology has been widely used to enhance content representation through multidimensional visualization. Television stations utilize AR to capture viewers' attention in the programs they broadcast; AR has the potential to enhance communication between viewers and the content. Our research on developing an AR application for an engaging immersive reality implementation aims to simulate a virtual stage in TV broadcasts, displaying real-time weather data from the Indonesian Meteorology, Climatology, and Geophysics Agency (BMKG) using the latest SQL database. The implementation of the AR system as a multimedia mode in delivering weather information increases the attractiveness and engagement of viewers. This system operates by translating weather data from SQL into key parameters for pre-built 3D visualizations, which appear at marked coordinates. This application runs on the Windows platform and can be managed via Android, allowing presenters to convey engaging scenarios. Research on East Java BMKG data showed that the design function to transform BMKG data into a virtual weather animation data was significantly successful in both synchronizations.